PENGARUH FASILITAS WISATA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN NUSANTARA DI KEBUN RAYA BOGOR - Wildan Rizky Rahadian (Bogor Hospitality Journal, 2021)
The purpose of this study was to determine the effect of facilities and service quality on tourist satisfaction at the Bogor Botanical Gardens, especially domestic tourists. This study was designed with a quantitative approach and accidental sampling as a sampling technique to obtain data by using a questionnaire as a data collection tool. As for testing the effect of the variables studied, the author uses multiple regression analysis techniques. From the test results, the value of the coefficient of determination (R2) is 58.5 which shows that there is an influence of tourist facilities and service quality on tourist satisfaction, while the other 41.5% is a variable that is not included in the study. The implication of this research is that the management of the Bogor Botanical Gardens needs to pay attention to and maintain tourist facilities and service quality in order to create loyalty as a form of tourist satisfaction.